The impact of financial literacy on risk seeing and patient attitudes of university students - Mudzingiri, Calvin (Taylor & Francis, 2021)
The study investigates the impact of financial literacy on risk preference and time preference choices of university students. The study collected data using a questionnaire, implemented a multiple price lists experiment, and administered a financial literacy test. A maximum of 7680 risk preference and 7680 time preference choices were elicited from the subjects. The study used a maximum likelihood joint estimation on an expected utility exponential function on homogeneous and heterogeneous preferences of students. Research results show that financial literacy significantly influenced risk and time preferences of university students with low financial literacy. The study also found significant risk aversion and impatience on homogenous preference choices of students. Structural behavioural errors were significant for the risk preference and time preference tasks choices. An increase in financial literacy is associated with risk seeking and patient attitudes among university students. These traits are associated with better life outcomes of citizens.
Keywords: Risk preferences; Time preferences; Financial literacy; Risk seeking; Patient; Multiple price list